Enhancement of Virus Infection Using Dynamic Cell Culture in a Microchannel - Jeong A Kim; Hye Jin Choi; Chul Min Kim; Hee Kyung Jin; Jae-sung Bae; Gyu Man Kim (Micromachines, 2018)
With increasing interest in induced pluripotent stem cells (iPSCs) in the field of stem cell research, highly efficient infection of somatic cells with virus factors is gaining importance. This paper presents a method of employing microfluidic devices for dynamic cell culture and virus infection in a microchannel. The closed space in the microchannel provided a better environment for viruses to diffuse and contact cell surfaces to infect cells. The microfluidic devices were fabricated by photolithography and soft lithography. NIH/3T3 fibroblast cells were cultured in the microfluidic device in static and dynamic conditions and compared with the conventional culture method of using Petri dishes. Virus infection was evaluated using an enhanced green fluorescent protein virus as a model. Dynamic culture in the microchannel showed similar growth of cells to that in Petri dish culture, but the virus infection efficiency was four-times higher. The proposed dynamic culture system could be useful in iPSC research by providing efficient virus infection tools.